The impact of competition mode and verbal encouragement on physiological, physical, and technical performances in youth football - Akdag, M.; Seibert, J.; Rumpf, M. C.; Lochmann, M. (International Journal of Sports Science and Coaching, 2025)
The present study compared the physiological, physical, and technical performances during "FUNino" (3 vs. 3) to that of the standard competition mode (7 vs. 7) under the influence of two coaching feedback situations (verbal encouragement vs. no verbal encouragement). "FUNino" features a 3-a-side game on a small pitch size (20 × 27-meter) with specific scoring rules (scoring within a 6 m goal zone) utilizing four small goals played without goalkeeper. There are also no offsides or throw-ins, however a kick- or dribble in. Sixteen U11 male youth footballers performed eight 10-min games, four in the "FUNino" and four in the standard competition game (7 vs. 7) in accordance to the German national government soccer association (DFB). All games were videotaped and physiological, physical, and technical parameters quantified for each game. A two-factors linear model with repeated measurement (ANOVA) were used to analyze the parameters. There were significant (p < 0.05) higher physiological (+7.10%), physical (+17.3%), and technical (+219%) parameters in the "FUNino" format. There were also significant higher physical (average (+8.88%) and relative (+5.47%) running distance) as well as technical (relative number of ball touches, + 9.69%) parameters in the feedback mode. "FUNino" provided a significant higher number of physiological, physical, and technical demands than the 7 vs. 7 used by the national soccer government association. Additionally, verbal encouragement positively influenced running distance. Competition format had greater influence on physiological, physical, and technical outcome compared to verbal encouragement.